2014
DOI: 10.1111/ajsp.12070
|View full text |Cite
|
Sign up to set email alerts
|

Cyber victimization and adolescent self‐esteem: The role of communication with parents

Abstract: Internet use has increased rapidly in recent years, and has inevitably led to some negative outcomes, notably cyber bullying and cyber victimization. The purpose of this study was to examine the effects of cyber victimization and parent-adolescent communication on self-esteem, and the moderating role of parent-adolescent communication in the relationship between cyber victimization and self-esteem among Turkish adolescents. The participants were 337 adolescents with a mean age of 16.37, (SD = 0.89). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 63 publications
3
20
1
Order By: Relevance
“…Contrary to other studies where high selfesteem was related to low aggressive tendencies or bullying (Donnellan et al, 2005;Özdemir, 2014;Patchin & Hinduja, 2010;Skues et al, 2005), the results from the study indicate the higher the level of self-esteem, the higher the level of tendency of bullying displays. This is similar to a few published study, which found that many bullies had higher levels of self-esteem and social success compared to victims (Koh & Wong, 2015;Menon et al, 2007;Salmivalli, 2010;Slee & Rigby, 1993;Volk et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to other studies where high selfesteem was related to low aggressive tendencies or bullying (Donnellan et al, 2005;Özdemir, 2014;Patchin & Hinduja, 2010;Skues et al, 2005), the results from the study indicate the higher the level of self-esteem, the higher the level of tendency of bullying displays. This is similar to a few published study, which found that many bullies had higher levels of self-esteem and social success compared to victims (Koh & Wong, 2015;Menon et al, 2007;Salmivalli, 2010;Slee & Rigby, 1993;Volk et al, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…In some studies, self-esteem was not correlated with bullying behaviour (Chen & Wei, 2011;Seals & Young, 2003;Thomaes, Bushman, Stegge & Olthof, 2008;Tritt & Duncan, 1997). However, there are a number of studies reported self-esteem is related to bullying behaviour in either positive (Koh & Wong, 2015;Menon, Tobin, Corby, Menon, Hodges, & Perry, 2007;Salmivalli, 2010;Slee & Rigby, 1993;Volk, Camilleri, Dane, & Marini, 2012;Yang, Kim, Kim, Shin & Yoon, 2006) or negative direction (Donnellan et al, 2005;Özdemir, 2014;Patchin & Hinduja, 2010;Skues, Cunningham & Pokharel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As for its relationship with cybervictimization, past studies have associated a poor self-concept with being cyberbullied by peers in preadolescent and adolescent samples [ 26 , 27 ]. Along these lines, Cole et al [ 28 ] found that, in a sample of 827 US students aged 8–13 who participated in a longitudinal study, cybervictimization significantly predicted an increase in negative self-perceptions, as well as cognitive reactions related to depression.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of cyberbullying, parental involvement can be beneficial for the child both in terms of stopping the bullying and in terms of emotional support (Fridh et al 2015;Özdemir 2014). In order for parents to offer adequate guidance and support, parental knowledge about the child's online activities and experiences is essential.…”
Section: Introductionmentioning
confidence: 99%